The asymmetric contagion effect from the U.S. stock market around the subprime crisis between 2007 and 2010. Issue 1 (1st January 2019) - Kao, Yu-Sheng; Zhao, Kai; Ku, Yu-Cheng; Nieh, Chien-Chung
Abstract: This study employed Enders and Siklos asymmetric co-integration frameworks, including the momentum threshold autoregressive (M-TAR) and logistic smooth transition co-integration (LSTC) models, to investigate whether contagion effects had existed in international stock markets by using the changes in the asymmetric co-integration relationships between the U.S. S&P 500 Index and a total of 23 markets in Asia, Europe, and America during the subprime crisis. The main findings demonstrated that the subprime crisis did not reinforce co-movement trends between the S&P 500 Index and these stock markets, by the application of the Engle-Granger (1987) symmetric co-integration test. However, with the application of the asymmetric co-integration frameworks, both M-TAR and LSTC showed there existed contagion effects between them in the aftermath of Lehman Brothers' bankruptcy in 2008; transition speeds between these two regimes also substantially increased in the LSTC during the financial crisis. Only the Chinese market was not affected by the U.S. market during this crisis; only an interdependence effect existed between the U.S. and China. The subprime crisis determined the degree of contagion, depending on the financial linkage to the U.S. market, which further demonstrates the differences in the causes and influence between the subprime crisis and other financial crises in emerging markets.